2014
DOI: 10.3402/ljm.v9.25391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan on physical capacities of North African boys fasting for the first time

Abstract: IntroductionMost of the literature related to the effects of Ramadan fasting on physical performance has focused on adults, and only three studies have examined its impact on children’s physical performance.AimsTo examine the effects of Ramadan fasting on first-time fasting boys’ performance in short-term explosive exercises [vertical and horizontal jump tests (VJT and HJT), 20-m and 30-m sprints and medicine-ball throw (MBT)], as well as in sub-maximal endurance [6-min walking distance (6MWD) measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(67 citation statements)
references
References 48 publications
2
63
2
Order By: Relevance
“…A small reduction in body mass during RIF was noticed in this study, although the difference was not statistically significant as also reported by Ramadan15 and Fenneni et al 18. This finding was contradictory to the earlier findings which reported a significant change in body mass during the month of Ramadan 19–21.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…A small reduction in body mass during RIF was noticed in this study, although the difference was not statistically significant as also reported by Ramadan15 and Fenneni et al 18. This finding was contradictory to the earlier findings which reported a significant change in body mass during the month of Ramadan 19–21.…”
Section: Discussioncontrasting
confidence: 93%
“…Meckel et al 2 reported that reduced carbohydrate consumption during RIF might be the contributory factor towards reduced muscle glycogen store that in turn might be one of the responsible factors towards the decrease in body mass 2. According to Fenneni et al ,18 the insignificant change of body mass during RIF in both the groups (EG and CG) might be most likely due to the fact that the fat-free mass did not change during the study (although it is a limitation that the fat-free mass was not categorically measured in this study). On the other hand, a decrease in powerful performances during RIF was attributed to the decrease in fat-free mass 24…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a control group makes it difficult to evaluate the observed change in the context of the normal expected body mass change in children of similar age groups. However, in a recent study, 17 North African boys of a similar age showed no changed in body weight after 1 month of Ramadan fasting. Previous studies have reported a decrease in body fat percentage in adult athletes during Ramadan,9,34 although there was no significant change in body fat percentage in this cohort.…”
Section: Discussionmentioning
confidence: 82%
“…15,16 A few studies have investigated the effects of Ramadan fasting in children, although they have mainly focused on sports-specific outcomes. [17][18][19] Because children are actively growing, their nutritional requirements and energy expenditures are quite different from those of adults. The potential negative consequences of Ramadan fasting on body composition, physical activity, sleep, and cognitive ability may impact their ability to successfully engage in active learning at school.…”
mentioning
confidence: 99%
“…It occurs during the ninth month of the Islamic lunar calendar, during which healthy adult Muslims abstain from food and fluid intake from dawn (el fajr) to sunset for approximately 30 days [56]. The duration of the daytime fast varies and is significantly impacted by the location and season.…”
Section: Ramadan Intermittent Fastingmentioning
confidence: 99%